Advances in Nanoparticles: Synthesis, Characterization, Theoretical Modelling, and Applications - Pasquini, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book focuses on recent advances in the synthesis of nanoparticles, their characterization, and their applications in different fields such as catalysis, photonics, magnetism, and nanomedicine. Nanoparticles receive a large share of the worldwide research activity in contemporary materials science. This is witnessed by the number of scientific papers with ""nanoparticle"" as a keyword, increasing linearly in the last 10 years from about 16,000 in 2009 to about 50,000 in 2019. This impressive widespread interest stems from the basic science of nanoparticles, which constitute a bridge between the molecular and the bulk worlds, as well as from their technological applications. The preparation of nanoparticles is a crossroad of materials science where chemists, physicists, engineers, and even biologists frequently meet, leading to a continuous improvement of existing techniques and to the invention of new methods. The reader interested in nanoparticles synthesis and properties will here find a valuable selection of scientific cases that cannot cover all methods and applications relevant to the field, but still provide an updated overview on the fervent research activity focused on nanoparticles.